PENEGAKAN HUKUM PIDANA TERHADAP TAWURAN PELAJAR DI KOTA YOGYAKARTA - Fiqri, Muhamad Saikul; Wibowo, Ari (Universitas Nurul Jadid, 2024)
This study discusses law enforcement and obstacles in enforcing criminal law against student brawls in the city of Yogyakarta. This type of research is empirical legal research with a sociological approach. The data sources consist of primary data in the form of interviews and secondary data in the form of primary, secondary and tertiary legal materials. Methods of collecting data by interview and literature study. The results of this study are, first, the DIY Education, Youth and Sports Office and the Yogyakarta City Resort Police have taken steps to enforce criminal law in the form of increasing coordination between the police and the school regarding security and student safety; as well as Conducting counseling related to the dangers of student brawls and narcotics abuse by students. Second, the obstacles faced by the DIY Education, Youth and Sports Office and the Yogyakarta City Resort Police are the lack of involvement of parents in raising and teaching their children to behave positively and not harm others; Lack of prevention efforts made by the school, such as facilitating permission to leave lessons or school; Parents who don't pay much attention to their children and seem to let their children go unsupervised; In carrying out law enforcement, the investigation process is not carried out by child investigators because the number of child investigators is small.